THE EFFECT OF GROUP INVESTIGATION–TYPE COOPERATIVE LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES AT GRADE V SD NEGERI 101859 RAMBAI ACADEMIC YEAR 2019/2020 - Feronika Tarigan; Rumiris Lumbangaol; Patri Janson Silaban (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research utilized a descriptive method which was conducted in one class, namely the experimental class. The instrument used to collect data was multiple choice questions. The hypotheses were examined by the "t" test. The results of statistical calculations revealed that Group Investigation learning model significantly influenced the studets’ learning outcomes on the material of “Lingkungan Sahabat Kita” sub-theme of environmental changes at grade VSD Negeri 101859 Rambai the academic year 2019/2020. This was supported by the average score in posttest which was in the excellent category. Based on the research results, Group Investigation type cooperative learning model gave a significant effect on students’ learning outcomes with tcount > ttable (9.385 > 1.6838) at the significant level α = 0.05. Thus, Ha was accepted and Ho was rejected. After that, the result of t-test data analysis found that tcount > ttable (1.449> 1.683851) at a significant level of 5%. It can be concluded that hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, this learning model was feasible to be implemented in the learning process, especially in influencing better learning outcomes.